World Agricultural Forum 2017 - Food Security and The “Terrorist Within Us” - Lim, Christopher (2017)
During the recent World Agricultural Forum (WAF) 2017 Conference, jointly organised with RSIS in Singapore, the role of cross border trade on food security was examined. Another related but under-discussed topic, is food safety.